Orthopedic Manifestations of Mobius Syndrome: Case Series and Survey Study - Philip McClure; David Booy; Julia Katarincic; Craig Eberson (International Journal of Pediatrics)
Background. Mobius Syndrome is a rare disease defined by bilateral congenital 7th nerve palsy. We focus on reporting the prevalence of orthopedic disease in this population. Methods. Twenty-three individuals with Mobius Syndrome underwent orthopedic physical examination, and additional 96 patients filled out a survey for self-reported orthopedic diagnoses. Results. Clubfoot was present in 60% of individuals in the physical exam series and 42% of those in the survey. Scoliosis was present in 26% and 28%, respectively. Poland’s Syndrome was present in 17% and 30%. In addition to these findings, 27% of patients reported having difficulty with anesthesia, including difficulty in intubation and airway problems. Conclusion. An increased prevalence of scoliosis, clubfoot, transverse limb deficiencies, and Poland’s Syndrome is identified in the setting of Mobius Syndrome. In the setting of several deformities often requiring surgical correction, a high incidence of anesthetic difficulty is noted and should be discussed with patients and other providers during surgical planning.